Malignant Transformation Within Ovarian Dermoid Cysts: an Audit of Treatment Received and Patient Outcomes. an Australia New Zealand Gynaecological Oncology Group (ANZGOG) and Gynaecologic Cancer Intergroup (GCIG) Study. Issue 1 (1st January 2010) - Gainford, M. Corona; Tinker, Anna; Carter, Jonathan; Petru, Edgar; Nicklin, Jim; Quinn, Michael; Hammond, Ian; Elit, Laurie; Lenhard, Miriam; Friedlander, Michael
Abstract : Introduction: Malignant transformation in an ovarian dermoid cyst occurs in 1% to 2% of cases. Our knowledge about this tumor type is limited and largely based on case reports. We aimed to collate and analyze the cumulative experience of how these patients have been managed in an effort to identify the most appropriate treatment strategies. Methods: A survey was sent to the members of the Gynaecologic Cancer Intergroup. Data collected included age, symptoms, stage, extent of surgery, chemotherapy and radiotherapy details, response to treatment, progression, survival, and salvage therapy. Results: Data on 33 patients whose conditions were diagnosed between 1979 and 2007 were received from 10 centers in Australia, Canada, Germany, and Austria. The mean age was 49 years. All 15 patients with stage I disease and most of the patients with stages II and III were optimally debulked. Four patients with stage I disease had fertility-sparing surgery with good outcomes. Chemotherapy was not routinely given after surgery and did not seem to be effective. Platinum-based regimens were most commonly used. At relapse, 2 patients had a sustained remission after secondary surgery for relapsed disease. Second-line chemotherapy and radiotherapy were infrequently prescribed. Patients with stage I disease had a good outcome, with all but 2 alive and well at a minimum of 12 months of follow-up. Conclusions: Most patients undergo optimal debulking surgery. Fertility-sparing surgery may be a reasonable option in selected patients. Stage I patients have a good prognosis. There is no standard adjuvant treatment, but platinum-based regimens are most commonly used. However, regardless of treatment received, patients with advanced disease do poorly.